Dekonstruksi Peran Seme dan Uke dalam Manga Shishi mo Kobamazu - Vanya Arisda Putri; Diana Puspitasari; Heri Widodo (KIRYOKU, 2022)
This research is descriptive qualitative research with the object of research manga entitled "Shishi mo Kobamazu" (2014) by Kiriyu Kiyoi. This manga is a boy's same-sex love genre that generally has a formula for the roles of Seme and Uke. The role of seme will be considered to have all the masculine traits and the role of uke to have all the feminine traits. In the Shishi mo Kobamazu manga, the roles of Seme and Uke are given a different role concept from manga boy's love in general resulting in a deconstruction of the role concepts of Seme and Uke. The aim of this research is to describe the deconstruction that occurs and its depiction in literary works so that it can be seen that the construction of gender roles in same-sex love relationships does not have a patent provision and can change according to conditions and times. The method used is a literature study. The theory used in this research is Derrida's deconstruction theory and Butler's performativity. Both theories are used to analyze the form of deconstruction in the roles of seme and uke and to understand the concept of gender roles in same-sex relationships. The results show that the character in this manga can display and form a new identity in their seme and uke roles through the performativity of gender roles in same-sex relationships. The new identity in the form of Seme and Uke is not fixed on one gender trait. Seme can be described as having a petite body and characters like women and uke can be described as having a strong and masculine physique. The roles of Seme and Uke can change according to the identity shown by each character in the manga.